PENGARUH GREEN BEHAVIOR INDUSTRI KECIL, TEKNOLOGI RAMAH LINGKUNGAN, DAN PENDAPATAN TERHADAP KEBERLANJUTAN LINGKUNGAN DI KOTA DENPASAR - Hosana Laura Pusparatri; Amrita Nugraheni Saraswaty (CV. Adiba Aisha Amira, 2026)
Small industries in urban areas play an important role in the economy, yet they can increase environmental pressure if not supported by environmentally responsible behavior and production practices. This study examines the effects of Small-Industry Green Behavior, Environmentally Friendly Technology, and Income on Environmental Sustainability among 58 small-industry actors in Denpasar City using a quantitative associative approach and multiple linear regression. The simultaneous test indicates that the three variables significantly affect environmental sustainability. Partially, green behavior has a positive and significant effect, environmentally friendly technology has a positive but insignificant effect, and income has a negative and significant effect; green behavior is the most dominant predictor. These findings highlight the need to strengthen green practices, support the adoption of environmentally friendly technologies, and expand training and assistance so that income growth aligns with stronger environmental commitment.